Quality of life in patients with heart failure and improved ejection fraction: one year changes and prognostic implication. (3rd October 2022) - Gonzalez, B; Zamora, E; Rivas, C; Pulido, A; Crespo, E; Velayos, P; Diaz, V; Altabella, M; Bares, D; Codina, P; Domingo, M; Santiago-Vacas, E; et al.
Abstract: Background: Inconsistent and controversial results have been reported about the association of quality of life (QoL) and left ventricular ejection fraction (LVEF) in patients with heart failure (HF). The 2021 universal definition of HF specifically describes the criteria for the patients with HF and improved LVEF (HFimpEF): HF with a baseline LVEF ≤40%, a ≥10 point increase from baseline LVEF, and a second measurement of LVEF >40%. Purpose: 1) To assess whether patients with HF and reduced LVEF (HFrEF) at first visit in an outpatient HF Clinic that fulfil the HFimpEF criteria one year later presented a higher improvement in QoL assessed by the Minnesota Living With Heart Failure Questionnaire (MLWHFQ) than those patients that did not fulfil HFimpEF criteria. 2) To assess the prognostic role of QoL on outcomes in HFimpEF patients. Methods: In a prospective registry of real-life HF outpatients LVEF and QoL evaluated by MLWHFQ were assessed at first visit at the HF Clinic and at one year of follow-up. Results: From August 2001 to August 2021, baseline and one year LVEF and MLWFQ scores were available in 1040 patients with an initial LVEF ≤40%. Table 1 shows baseline demographic and clinical characteristics of patients. In summary, mean age was 65.2±11.7 years, 75.9% of the patients were men, the main aetiology was ischaemic heart disease (52.9%) and patients were mostly in New York heart Association (NHYA) class II (71.1%) and III (21.6%). Baseline LVEF was 28.5% ± 7.3 and baseline MLWHFQ score was 30.2±19.5. At one year, mean LVEF increased to 38.0±12.2 while MLWHFQ scores improved to 17.4±16.0. There were 361 patients that fulfilled the HFimpEF criteria (34.7%). These patients significantly and markedly improved both LVEF (from 28.7±6.6 to 50.9±7.6, p<0.001) and QoL (from 32.9±20.6 to 16.9±16.0, p<0.001). Although in patients that did not fulfil the criteria of HFimpEF both LVEF (from 28.4±7.6 to 31.1±7.9, p<0.001) and QoL (from 28.7±18.8 to 17.6±15.9, p<0.001) also significantly improved, the improvement in QoL was significantly higher in HFimpEF patients (−16.0±23.8 vs. −11.1±20.3, p=0.001), taking into account that baseline MLWHFQ score was worse in HFimpEF patients (p=0.001). However, at one year QoL was similar when both groups were compared (p=0.50). MLWHFQ score at one year proved to be superior to QoL improvement (using a cut-off of at least 5 points) from the prognostic point of view. Conclusions: QoL improved both in patients with and without HFimpEF criteria, and QoL perception at one year was similar in both groups, suggesting the influence of other factors other than LVEF in QoL perception. QoL at one year revealed to be superior to QoL changes from baseline from the prognostic point of view. Funding Acknowledgement: Type of funding sources: None.